2006
DOI: 10.1155/2006/307324
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Colonic Stenting as a Bridge to Curative Surgery in Patients with Acute Left-Sided Malignant Colonic Obstruction: A Canadian Perspective

Abstract: The cost-effectiveness of colonic stenting as a bridge to curative surgery in patients with acute left-sided malignant colonic obstruction: A Canadian perspective. Can J Gastroenterol 2006;20(12):779-785.BACKGROUND: Over the past several years, colonic stenting has been advocated as an alternative to the traditional surgical approach for relieving acute malignant left-sided colonic obstruction. The aim of the present study was to determine the most cost-effective strategy in a Canadian setting. PATIENTS AND M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
(30 reference statements)
1
18
0
4
Order By: Relevance
“…However, hospital stay was longer in patients with diverting stoma than in patients with no stoma, because they needed some time to learn how to handle the stoma appliance [14]. Moreover, diverting stoma also increases patient discomfort, overall cost, and the duration of hospitalization since the patient will need a second operation for closure of the stoma [17,18]. Phatak et al [19] reported that diverting ileostomies are associated with a significant risk for ileostomy-related morbidity including dehydration and perioperative complications of stoma closure.…”
mentioning
confidence: 99%
“…However, hospital stay was longer in patients with diverting stoma than in patients with no stoma, because they needed some time to learn how to handle the stoma appliance [14]. Moreover, diverting stoma also increases patient discomfort, overall cost, and the duration of hospitalization since the patient will need a second operation for closure of the stoma [17,18]. Phatak et al [19] reported that diverting ileostomies are associated with a significant risk for ileostomy-related morbidity including dehydration and perioperative complications of stoma closure.…”
mentioning
confidence: 99%
“…In our study, the recanalization rate, although with a small sample size and with no statistical significance, was higher in BG compared to SG, probably due to resolution of occlusions and an improvement in global clinical and nutritional assessment. SEMS insertion and a delay in surgical intervention appears to reduce the mean time of hospital stay, to 13.5±3 days, compared to 16.1±7.7 days in SG, as described in the literature (17)(18)(19)(20), and this leads to significant cost-saving. We explain the reduction in the length of hospital stay by a lower rate of early complications between the two procedures (stenting and surgery) ( Table 5) and by a lower rate of early complication between urgent surgery and delayed surgery (Table 6), although this latter data was not statistically significant.…”
Section: Discussionmentioning
confidence: 69%
“…A Canadian study based on a decision analytical model even suggested that the use of colonic stenting for patients with acute malignant colonic obstruction is less expensive than emergency resective surgery [20] . Whether this is so, in fact, cannot be confirmed and should be prospectively proven by true comparative studies.…”
Section: Commentary On Hot Topicsmentioning
confidence: 99%